PERANCANGAN DESAIN KONTEN MEDIA SOSIAL UMKM MELLINT PASTRIES SEBAGAI MEDIA PROMOSI - Yuwono, Budi; Ghani, Oktaviani (LP2M Sekolah Tinggi Seni Rupa dan Desain Visi Indonesia (STSRD VISI), 2024)
Social media is a powerful promotional tool due to its rapid and extensive reach. Instagram, in particular, has become a popular platform for promotional activities. Mellint Pastries, an online cake business, utilizes Instagram for promotion but has not fully optimized its marketing strategy on the platform. This research aims to enhance Mellint Pastries' Instagram presence to reach a broader audience and boost sales. The study focuses on designing and visualizing Instagram content as an alternative promotional medium for Mellint Pastries. Using qualitative research methods, including interviews, observations, and literature review, the research aims to describe the design process and objectives for Mellint Pastries' Instagram content.